2015
DOI: 10.1152/ajpregu.00267.2014
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 enhances skeletal muscle regeneration in mice

Abstract: Activation of muscle progenitor cell myogenesis and endothelial cell angiogenesis is critical for the recovery of skeletal muscle from injury. Angiopoietin-1 (Ang-1), a ligand of Tie-2 receptors, enhances angiogenesis and skeletal muscle satellite cell survival; however, its role in skeletal muscle regeneration after injury is unknown. We assessed the effects of Ang-1 on fiber regeneration, myogenesis, and angiogenesis in injured skeletal muscle (tibialis anterior, TA) in mice. We also assessed endogenous Ang-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 49 publications
6
41
0
Order By: Relevance
“…Many FREPs, like tenascin [49], fibrinogen-like protein [50], angiopoietin [51], and hepassocin [52], have been reported to be involved in the regulation of regeneration. These FREPs showed an obvious genome-wide gene duplication in A .…”
Section: Resultsmentioning
confidence: 99%
“…Many FREPs, like tenascin [49], fibrinogen-like protein [50], angiopoietin [51], and hepassocin [52], have been reported to be involved in the regulation of regeneration. These FREPs showed an obvious genome-wide gene duplication in A .…”
Section: Resultsmentioning
confidence: 99%
“…Although the importance of angiopoietin signaling in the vasculature is well defined, the cellular origins and functional roles of these two factors in skeletal muscle have only recently received attention. ANGPT1 is the principal angiopoietin produced by skeletal myoblasts and myotubes and is an important regulator of myogenesis and angiogenesis (38,42). Conversely, ANGPT2 has no effect on myoblast proliferation and migration and exerts a relatively weak and context-dependent effect on angiogenesis (41).…”
Section: Skeletal Muscle Angiogenic Signalingmentioning
confidence: 99%
“…Conversely, ANGPT2 has no effect on myoblast proliferation and migration and exerts a relatively weak and context-dependent effect on angiogenesis (41). Mofarrahi et al (42) recently showed that overexpression of ANGPT1 following muscle injury in mice promoted capillary growth and accelerated the recovery of contractile performance. In this scenario, it is noteworthy that TH induced the expression of ANGPT1 in skeletal muscle (Fig.…”
Section: Skeletal Muscle Angiogenic Signalingmentioning
confidence: 99%
“…Although we saw efficient expression of our AAV in myofibers, we observed no immunofluorescence co-labeling of CD31 + , SMA + , and our FLAG-tagged construct, suggesting that our AAV6 serotype more efficiently infected and/or expressed in muscle cells in vivo . It is possible that improved muscle cell survival resulted in enhanced ischemia-induced expression of vascular growth factors and subsequent angiogenesis 65, 66 . Prior studies of murine HLI have supported the idea that pre-existing collateral vessels and arteriogenesis are critical determinants of necrosis and perfusion recovery 67, 68 .…”
Section: Discussionmentioning
confidence: 99%